2003
DOI: 10.1093/jurban/jtg069
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social and Behavioral Science in Public Health Practice: A Study of the New York City Department of Health

Abstract: Studies over the last decade have demonstrated the effectiveness of public health interventions based on social and behavioral science theory for many health problems. Little is known about the extent to which health departments are currently utilizing these theories. This study assesses the application of social and behavioral science to programs in the New York City Department of Health (NYCDOH). Structured open-ended interviews were conducted with executive and program management staff of the health departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Doctors tend to focus on providing 'hard' medical care, and it is inevitable that the 'softer' behavioural aspects get neglected. Creation of environments conducive for learning require changes in policy, infrastructure, resource allocation and attitudes; however doing so will be beneficial not only for learning but also for furthering the standards of healthcare (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Doctors tend to focus on providing 'hard' medical care, and it is inevitable that the 'softer' behavioural aspects get neglected. Creation of environments conducive for learning require changes in policy, infrastructure, resource allocation and attitudes; however doing so will be beneficial not only for learning but also for furthering the standards of healthcare (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies confirmed the relation between mortality, behavioral and social factors such as tobacco use, poor diet, lack of physical exercise, use of drugs and alcohol as well as sexual behavior. Where these studies emphasized the importance of behavioral and social science to public health practice (2, 3).…”
Section: Introductionmentioning
confidence: 99%